The Effectiveness of the Use of Fluoridated Toothpaste on Reduction of Plaque Score: A Systematic Literature Review - Sunomo Hadi; Ossy Amalia Julfani; Bambang Hadi Sugito (Aloha International Journal of Health Advancement (AIJHA), 2021)
Introduction: Plaque is a biofilm consisting of a group of bacteria that attached to the surface of teeth, dental restorations, and prosthetic teeth. Periodontal disease occurs in many developed and developing countries and accounts for about 20-50% of the world's population. In Indonesia, periodontal disease is a disease of the teeth and mouth that is mostly suffered by the population, namely 70%. Dental plaque is an etiological factor that causes periodontal disease. Brushing your teeth is the way most often used to perform oral hygiene. Fluoride is another antimicrobial agent that is combined in toothpaste and mouth rinses to prevent plaque buildup on the surface of teeth. Purpose: To know the effectiveness of using fluoride toothpaste in reducing the plaque score. Methods: Literature review was carried out based on the inclusion and exclusion criteria to be reviewed. Of the 11 studies used, all of them used experimental research methods with the type of original publication articles. The experimental population has a broad coverage. Results: Based on literature review results in 11 journals, other general compositions of fluoridated toothpaste was stannous fluoride and sodium fluoride, and there was effectiveness after routine use of fluoridated toothpaste in reducing plaque scores. Keywords: fluoridated toothpaste; tooth brush; laque score